Assembly and activation of the death-inducing signaling complex - Elizabeth Fosuah; Zhangfei Shen; Jiale Xie; Chen Wang; Qingpeng Lin; Tian-Min Fu (Proceedings of the National Academy of Sciences, 2025)
The death-inducing signaling complex (DISC), comprising Fas, Fas-associated death domain (FADD), and caspase-8, initiates extrinsic apoptosis. Using cryogenic electron microscopy (cryo-EM), we show that Fas and FADD death domains (DDs) form an asymmetric 7:5 oligomer, which promotes FADD death effector domain (DED) filament formation. Structural analysis reveals that FADD DED filaments closely resemble caspase-8 tandem DED filaments, suggesting that FADD DED serves as a nucleation scaffold for caspase-8 assembly. These findings provide a mechanistic framework for how DISC assembly initiates apoptosis and amplifies signaling via higher-order oligomerization.